Investigating the Effectiveness of Emulsified Acid on Sandstone Formation under High Temperature Conditions - Ben Mahmud, Hisham; Norlee, Adeline; Tan, Inn Shi; Foo Chee Yew, Henry; Shafiq, Mian Umer (IOP Publishing, 2019)
Acid stimulation supports the oil and gas industry as a versatile mean in enhanced oil recovery to fulfill the world energy demand. Although hydrochloric acid can significantly improve the reservoir permeability, its rapid reaction rate at high temperature has created a barrier for acid penetration. Subsequently, emulsified acid has slowly gain its popularity due to its retardation effect which allows deeper penetration of acid into the formation and achieves minimal corrosion issues. Nonetheless, emulsified acid has rarely applied on sandstone formation. Since a large portion of reservoirs are made up of sandstone, the effects of emulsified acid on sandstone under high temperature conditions should be studied to unlock the effective usage of emulsified acid in restoring the hydrocarbon recovery from the potential sandstone reservoirs. Besides, it is also crucial to explore cheaper and greener substitute to formulate innovative emulsified acid in minimizing the high acidizing budget along with environmental concerns. In this project, 10 different emulsified acid combinations are prepared using hydrofluoric acid, hydrochloric acid, phosphoric acid, formic acid, acetic acid, cationic surfactant, diesel and waste oil. The pre-flush treatment (5 % CH3COOH: 10 % HCl) is followed by the main flush (emulsified acids) saturation for 3 days. The thermal stability of emulsified acids and their effect on the Berea sandstone properties are evaluated. Major outcome is that the emulsified acids have the capability to remain stable at 275 °F up to 6 hours with uniform and fine droplet size. It is also proven that most of the emulsified acids can improve the porosity and permeability of Berea sandstone core samples except for HF: H3PO4. Regardless of the types of oil used for emulsified acid formulation, HF: HCl acid combination shows the best performance enhancement for both diesel-based and waste oil-based emulsified acids. In sandstone acidizing, emulsified acid dissolves the minerals and create acid transport pathway with close connectivity between pore spaces, causing the formation of large and conductive channels within the rock. Hence, these positive results clearly reflect on the feasibility of emulsified acid application in sandstone matrix acidizing and the effectiveness of waste oil as a replacement fluid for diesel.